Analysis of the strength of the frame construction on the nyamplung bean peeling machine using the finite element method - Asep Dharmanto; Angger Haris Muzakki; Hilman Sholih; Aswin Domodite (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2025)
The frame of the nyamplung bean peeling machine is a very important component in this design, the frame functions as a fulcrum for the mechanical and electrical components. The problem that occurred during observations was that when testing the nyamplung bean peeling machine at maximum rotation, the frame experienced vibrations. The aim of this research is to determine the stress distribution and deflection resulting from static loading on the frame of the Nyamplung bean peeling machine and to compare hollow tube materials with angle iron, which of these two types of material is more efficient. The framework structure was designed and analyzed using Solidwork 2021 software. There are several tests used, but most often the computational method is used using the Finite Element Method (FEM). In frame 1 calculations using housing and crusher loading of 50kg. The results of the simulation obtained a bending strength of 18 N/mm2, while manual calculations obtained a result of 19.94 N/mm2. Permissible stress in ASTM A36 material 160 N/mm2. The displacement in manual calculations was found to be 0.120 mm, whereas using simulation it was 0.077 mm. In frame 2 the results obtained from manual calculations were with a bending stress of 13.84 N/mm2. And with simulation the results obtained were 13 N/mm2, and the displacement in manual calculations was obtained at 0.117 mm, whereas using simulation it was 0.08 mm